2015
DOI: 10.1080/0972060x.2014.895683
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial and Antiprotozoal Activity of Essential Oils FromVernonia brasiliana(Less) Druce (Asteraceae)

Abstract: Vernonia brasiliana (L) Druce is a plant from the Asteraceae family. The essential oils obtained by hydro distillation from flowers and roots of V. brasiliana were analyzed by GC and GC-MS for the first time. The major components found in the flowers were (E)-hex-2-enal (4.04 %), hexan-1-ol (4.23 %), (Z)-hex-2-en-1-ol (6.32 %), palmitic acid (8.30 %), and hexacosane (4.91 %). The roots presented as major components modheph-2-ene (8.69% ), α-isocomene (15.41 %), α-gurjunene (9.61 %), β-isocomene (10.26 %) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…Vernonia brasiliana : V. brasiliana is a bush tree observed in the Brazilian savannah, also known as ‘assa-peixe’. The EO from flowers, roots and leaves of V. brasiliana did not display cytotoxicity against Vero (ATCC CCL 81) and RAW 264.7 cell lines, but they showed inhibitory activity against T. cruzi (Martins et al ., 2015). The only study about V. brasiliana , by Martins et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vernonia brasiliana : V. brasiliana is a bush tree observed in the Brazilian savannah, also known as ‘assa-peixe’. The EO from flowers, roots and leaves of V. brasiliana did not display cytotoxicity against Vero (ATCC CCL 81) and RAW 264.7 cell lines, but they showed inhibitory activity against T. cruzi (Martins et al ., 2015). The only study about V. brasiliana , by Martins et al .…”
Section: Discussionmentioning
confidence: 99%
“…The only study about V. brasiliana , by Martins et al . (2015) showed that (a) in the EOs obtained by hydrodistillation, the major components found in the flowers were ( E )-hex-2-enal (4.0%), hexan-1-ol (4.2%), ( Z )-hex- 2-en-1-ol (6.3%) and palmitic acid (8.3%); (b) in the roots, the major components were α -isocomene (15.4%), α -gurjunene (9.6%), β -isocomene (10.3%), trans caryophyllene (10.4%) and palmitic acid (5.3%); (c) the major components of EOs in the leaves were trans -caryophyllene (8.7%), germacrene-D (10.2%) and caryophyllene oxide (4.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of antiparasitic activities have established that EOs can be highly active (IC 50 < 10 μg/mL), active (IC 50 > 10 < 50 μg/mL), moderately active (IC 50 > 50 < 100 μg/mL) or inactive (IC 50 > 100 μg/mL) (Estevam et al, 2017). Not only EL-EO and ES-EO exhibit strong leishmanicidal activity, but also other species of the family Asteraceae stand out as producers of active EOs against parasites of the genus Leishmania: Artemisia campestris (Aloui et al, 2016), Artemisia herba-alba (Tamargo et al, 2017), Artemisia absinthium (Tamargo et al, 2017), Artemisia abyssinica (Tariku et al, 2010), Vernonia brasiliana (Martins et al, 2015b) and Vernonia polyanthes (Moreira et al, 2017). Leishmanicidal activity exhibited by EOs from E. erythropappus can be explained by the high concentration of α-bisabolol, which had also been previously identified in EOs from Vanillosmopis arborea.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the action against T. cruzi trypomastigotes, the root EO was the most active (IC50: 70 μg/mL; SI = 3.1). The major compounds identified in this EO were modheph-2-ene (8.69%), agurjunene (9.61%), trans-caryophyllene (10.42%), β-isocomene (10.26%), and α-isocomene (15.41%) (Martins et al, 2015). Similarly, Moreira et al (2017) studied the effect of the EO from leaves of Vernonia polyanthes Less.…”
Section: Compounds From Vernonia Plants Are Active Against Trypanosommentioning
confidence: 93%